Trans-Generational Symbiont Transmission Reduced at High Temperatures in a West Nile Virus Vector Mosquito Culex quinquefasciatus - Tokash-Peters, Amanda G.; Jabon, Jaimy D.; Fung, Megan E.; Peters, Jessica A.; Lopez, Sergio G.; Woodhams, Douglas C. (Frontiers in Tropical Diseases, 2022)
The influence of environmental factors on the efficacy of the endosymbiont Wolbachia used in mosquito and pathogen control are poorly characterized and may be critical for disease control. We studied the vector mosquito Culex pipiens quinquefasciatus (Say) to determine the effect of temperature on the composition of the relative abundance of Wolbachia spp. and the microbiome, as well as key immune genes of interest in the Toll and IMD pathways. 16S barcode sequencing was used to determine the microbiome composition and qPCR was used to determine the relative abundance of Wolbachia spp. based on the highly utilized marker Wolbachia surface protein (wsp) gene. We found no effect of temperature within a single generation on the relative abundance of Wolbachia or immune gene expression, nor on the alpha or beta diversity of the microbiome. However, there was a significant difference in the abundance of Wolbachia between generations at high temperatures (≥ 28°C), but not at lower temperatures (≤ 23°C). These results support the idea that Wolbachia are reduced at higher temperatures between generations, which has an influence on the establishment of pathogens including West Nile Virus (WNV). Modulation of the Toll or IMD mosquito immune pathways was not indicated. Wolbachia endosymbiosis and trans-generation transmission appears especially sensitive to high temperatures, which may have implications for Wolbachia-based vector control strategies under climate change scenarios.